2021
DOI: 10.1088/1361-6560/ac279d
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Winston–Lutz test using reusable polyvinyl alcohol-iodide (PVA-I) radiochromic gel dosimeter

Abstract: Medical linear-accelerator-based stereotactic radiosurgery (SRS) using a stereotactic apparatus or image-guided radiotherapy system for intracranial lesions is performed widely in clinical practice. In general, Winston–Lutz (WL) tests using films or electric portal imaging devices (EPIDs) have been performed as pre-treatment and routine quality assurance (QA) for the abovementioned treatment. Two-dimensional displacements between the radiation isocentre and mechanical isocentre are analysed from the test; ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Therefore, recent studies have shown that the NIPAM 3D dosimeter can be used with CBCT for 3D scanning [72,73], and for the same purpose, a combination of a 3D gel dosimeter with MRI can be used to determine the radiation isocenter using the PAGAT and MAGAT dosimeters using the star-shot irradiation pattern [74][75][76][77]. The KI-PVA radiochromic gel dosimeter combined with the Winston-Lutz test was also used to determine the isocenter [78]. Recent work has demonstrated the use of PABIG nx [18] and VIPAR nd (VIP) [79] for radiation isocenter determination with CBCT and iCBCT reading and data In the case of 3D dosimeter measurements using NMR, MRI, CT, OCT, or USG, they should be moved to another room after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent studies have shown that the NIPAM 3D dosimeter can be used with CBCT for 3D scanning [72,73], and for the same purpose, a combination of a 3D gel dosimeter with MRI can be used to determine the radiation isocenter using the PAGAT and MAGAT dosimeters using the star-shot irradiation pattern [74][75][76][77]. The KI-PVA radiochromic gel dosimeter combined with the Winston-Lutz test was also used to determine the isocenter [78]. Recent work has demonstrated the use of PABIG nx [18] and VIPAR nd (VIP) [79] for radiation isocenter determination with CBCT and iCBCT reading and data In the case of 3D dosimeter measurements using NMR, MRI, CT, OCT, or USG, they should be moved to another room after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The data are processed using various software packages; for instance, for 2D calculations, myQA Machines (IBA, Schwarzenbruck, Germany), DoseLab (Varian, Palo Alto, CA, USA), FilmQA Pro™ (Ashland, Westmont, IL, USA), Mephisto (PTW, Freiburg, Germany), and polyGeVero-CT (v. 1.2, GeVero Co., Lodz, Poland), and for 3D calculations, polyGeVero-CT (v. 1.2, GeVero Co., Lodz, Poland) (Table 1). [25] All 2D and 3D dosimeters, such as film and gel dosimeters, rely on the radiationinduced responses of components sensitive to ionizing radiation. For instance, thin, flat 2D dosimeters (pos.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, gel dosimeters, which are chemical dosimeters, have been attracting significant attention as promising tools for measuring 3D dose distributions [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Various forms of chemical dosimeters are used, such as the Fricke gel dosimeter [ 22 , 23 , 24 ], which uses the oxidation reaction of iron ions, and the polymer gel dosimeter [ 25 , 26 , 27 ], which uses radiation-induced polymerization in a monomer solution.…”
Section: Introductionmentioning
confidence: 99%